+0  
 
+5
516
1
avatar
2x + 3y – z = 5
3x – 4y + 2z =1
4x – 6y + 5z = 7

Solve the simultaneous equations
Guest Feb 2, 2012
 #1
avatar+3077 
0
lappin:

2x + 3y – z = 5
3x – 4y + 2z =1
4x – 6y + 5z = 7

Solve the simultaneous equations


[input]solve( 2x + 3y - z = 5, 3x - 4y + 2z =1, 4x - 6y + 5z = 7 )[/input]
admin  Feb 2, 2012

32 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.